It’s in the out sides: An investigation into the cosmological contexts of South African jazz - Gamedze, Asher (School of African and GenderStuds, Anth and Ling, 2019)
This dissertation is an exploration of some of the philosophical thought and spiritual practices which constitute and are present and represented in and through certain instances of South African jazz. Amilcar Cabral’s revolutionary thought on liberation culture, which allows for thinking the radical impulse of cultural production, forms the foundation of the dynamic frame which we use to hear and think through the music’s content and the context by which it is composed. Through an engagement with the thought and music of the following artists - the Blue Notes, Miriam Makeba, Malombo, Nduduzo Makhathini, Zim Ngqawana, and a few others - we find ourselves in the presence of a liberatory tradition rooted in the cosmological worlds of Southern African people. Musical and spiritual practices of sangomas, the frequency of the maternal, medicinal relationships with plants and the land, and the communion and communication with ancestors are all channels of South African jazz. And the spirit of liberation that emerges in the music is situated in and dances through an encounter between these practices and aesthetics of the Black radical tradition. I provoke and elaborate on this encounter, considering the ambivalent, sometimes invisible, place of Africa in that tradition. Africa’s epistemological absence in much of the Black radical tradition, beyond minor essentialised and, at times, romanticised notions of an irretrievable source, a point of origin, or a site generally relegated to the past, is mirrored by the possibility of a productive synthesis which is improvised through the music. Moving with and for the music, listening to its critique of much of the writing about it and what that writing misses, I make the claim for jazz as a cosmologically-rooted African art form, forming part of a broader liberatory tradition which needs to be heard in relation to the spiritual and philosophical traditions which it extends.